Electronic imaging in astronomy detectors and instrumentation - McLean, Ian S. (Wiley-Praxis series in astronomy and astrophysics, 1997)
This book describes the remarkable developments that have taken place in astronomical detectors and instrumentation in recent years, from the invention of the charge-coupled device, or CCD, in 1970, through to the current era of Very Large Telescopes - the Keck telescopes in Hawaii, the ESO VLT, and GEMINI telescopes - and electronic imaging with space-borne instruments such as the Hubble Space Telescope.